A dimens\~ao político-relacional das políticas de mercado de trabalho no Brasil: A agenda deliberativa do Codefat - Sandro Pereira Silva (Instituto de Pesquisa Econômica Aplicada (IPEA), 2019)
– The purpose of this paper was to analyze the political role of the Deliberative Council of the Worker Support Fund (Codefat) in the process of coordination and participatory deliberation within the Public System of Employment, Work and Income (SPETR). As inputs, the minutes of all meetings of the council from its creation in 1990 until the end of 2016 were analyzed, identifying the matters subject to deliberation. It was found that on several occasions the Codefat had to face external interferences, generating instability in its deliberative potential, in function of the efforts of different coalitions of interest to have greater control over the financial resources that circulate around the Worker Support Fund (FAT). These interests, on the other hand, do not come only from representations related to capital and labor, since government representation also acts actively to assert its own interests, which focus mainly on the discussions about the budget dynamics of the FAT, in order to bring control over current revenues and expenses. In this sense, it is possible to affirm the existence of an overlapping of bureaucratic spaces of command with different structures of power, which in practice constitutes a "hierarchy of decision-making power".
Keywords: J58; 330; participative deliberation; public system of employment; hierarchy of decision-making power; Codefat; FAT